Prototipe Turntable Otomatis Dengan Kontroller PWM Motor DC Berbasis Arduino Uno R3 - Apriyanto, R. Akbar Nur (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2023)
Abstract - Train is one of the transportations used in Indonesia. With that, maintenance from facilities and infrastructure such as turntables is needed. Serves to change the direction of the train by detouring. Turntables are still done with a manual work system in some Daop in Indonesia. With that, this study aims to design a turntable work system automatically using Arduino Uno and sensors. The sensor used is an infrared sensor that functions as a detector for trains to come in the appropriate position and ultrasonic sensors function to also detect the distance of the train, these two sensors support each other for the perfection of the train being on the turntable, and assisted by a DC motor as a Turntable player. The distance is the magnitude of the duration divided by 58.2. When the infrared sensor condition in is high and the distance of the ultrasonic sensor is also met, the buzzer will sound. The buzzer will continue to sound and the DC motor will continue to rotate until 180o. When the rotation has reached its maximum position is characterized by the detection of the locomotive on the second infrared sensor (out).